Experimental results and thermodynamic analysis of a natural gas small scale cogeneration plant for power and refrigeration purposes - Bazzo, Edson; De Nacif Carvalho, Alvaro; Matelli, José Alexandre [UNESP] (Elsevier, 2013)
In this work, experimental results are reported for a small scale cogeneration plant for power and refrigeration purposes. The plant includes a natural gas microturbine and an ammonia/water absorption chiller fired by steam. The system was tested under different turbine loads, steam pressures and chiller outlet temperatures. An evaluation based on the 1st and 2nd Laws of Thermodynamics was also performed. For the ambient temperature around 24°C and microturbine at full load, the plant is able to provide 19 kW of saturated steam at 5.3 bar (161 °C), corresponding to 9.2 kW of refrigeration at -5 °C (COP = 0.44). From a 2nd law point-of-view, it was found that there is an optimal chiller outlet temperature that maximizes the chiller exergetic efficiency. As expected, the microturbine presented the highest irreversibilities, followed by the absorption chiller and the HRSG. In order to reduce the plant exergy destruction, it is recommended a new design for the HRSG and a new insulation for the exhaust pipe. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Absorption chiller; Cogeneration; Microturbine; Natural gas; Absorption chillers; Exergetic efficiency; Exergy destructions; Laws of thermodynamics; Micro turbine; Outlet temperature; Thermo dynamic analysis; Absorption cooling; Cogeneration plants; Cooling systems; Refrigerators; Thermoanalysis; Thermodynamics; Turbines; Refrigeration